The Oral Examination, Oral Cancer and Pre-Cancer - Easwar Natarajan; Ellen Eisenberg; Miranda Jennings (Association of American Medical Colleges, 2013)
Abstract The oral cavity is a key anatomic location. Yet in the course of professional training of physicians, dentists, and other health professionals, it is often given only modest attention. This module emphasizes the importance of the oral examination as a component of the general physical examination, and its role in the routine screening for oral cancer and lesions with malignant potential. This resource may be used as an educational and training component of the curriculum in physical examination and clinical diagnosis for students (i.e., medical, dental, nursing and allied health professions), and both medical and dental residents. This module consists of two separate learning segments. The first segment, titled The Oral Examination, is a narrated PowerPoint with an embedded video demonstration of how to conduct a proper oral examination. Emphasis is placed on visualization of the facial skin, palpation of the neck, and intraoral examination technique. The anatomy of the oral cavity and commonly occurring oral findings are illustrated and discussed. The module introduces oral cancer and precancer which are discussed more fully in the following segment. The second segment, titled Oral Cancer and Precancer, is also a narrated PowerPoint presentation, and a continuation of what was presented in the first segment. The key pathogenetic and clinical aspects of oral squamous cell carcinoma and its precursor lesions are presented. An in-depth discussion of the classic patient profile and contemporary information about the pathogenesis of oral squamous cell carcinoma are highlighted.